Proximate Analysis on Chayote (Sechium edule (Jacq.) Swartz) Sticks - Hijrawati Hijrawati; Jamaludin M Sakung; Tahril Tahril (Fakultas Kedokteran Universitas Sultan Ageng Tirtayasa, 2024)
Chayote is one type of commodity vegetables in Indonesia. It is known chayote has a high content of nutrients. The nutritional content in chayote can be efficacious as an antioxidant, antipyretic, anti-inflammatory, can reduce cholesterol levels, and hypertension. Processing of chayote into flour is so that it can be stored longer and can be processed into various snacks as desired. Chayote sticks are one of the innovations in food processing from chayote fruit flour. This study aims to determine the proximate levels of chayote sticks. The sample is crushed, then analyzed for protein content using a biuret reagent. Determination of protein levels using UV-Vis spectrophotometer at a wavelength of 549 nm and using a standard solution of bovine serum albumin as a comparison. Analysis of carbohydrate content using anthrone reagent. Determination of carbohydrate levels using UV-Vis spectrophotometer at a wavelength of 360 nm and using a standard solution of glucose as a comparison. Analysis of fat content using the soxhlation method. Determination of fat content using soxhlet tool with N-hexane as solvent in sample extraction. Analysis of water content using gravimetric method. Determination of water content using an oven tool. Analysis of ash content using gravimetric method. Determination of ash content using a kiln. The results of this study showed proximate levels in chayote sticks were that the average protein content of 10.157%, the average carbohydrate content of 49.873%, the average fat content of 32.688%, the average water content of 0.42%, and the average ash content of of 2.174%.